Microfibre release due to domestic washings: an overview from textile fuzzing perspective / Eryna Nasir, Suzaini Abdul Ghani and Noor Najmi Bonnia - Nasir, Eryna; Abdul Ghani, Suzaini; Bonnia, Noor Najmi (Universiti Teknologi MARA (UiTM), 2022)
Microfibre release into the aquatic environment is one of the latest research interests and washing activities at home or also known as domestic washings have been claimed as one of the sources of the of this problem. Washing, textile and ageing parameters are among the factors that influence microfibre release and some approaches for MF release mitigation are discussed. The main factor of the fibre loss from the textile materials is due to the entanglement of small fibres on the fabric surface during wearing or care activities. Hence, the review from the context of textile surface fuzzing is needed to understand the phenomenon better especially for the evaluation purpose. The microfibre release from textile materials during washing is due to the detachment of the fibres either prior to or after pilling formation. In any of these situations, some amount of microfibres or fuzzing are left on the textile surface. Therefore, the evaluation on the fuzzing is proposed to see if it has a relationship with the amount of microfibres being released into the washing effluent. The evaluation of textile fuzzing is usually made by either physical test or digital image processing, which the latter offers more objective results.